A Philosophical Assessment of Non-Possessiveness in Teaching and Learning (Global Journal of Human-Social Science, 2020)
Education involves teaching and learning to gather information, improve knowledge, and develop skills. Corresponding value-oriented conduct is required to give a meaningful orientation to such a process. The object of value-oriented conduct as a subject matter of education ethics is to seek the development of a human being as a being capable of understanding, sympathy, and communication with all members of the human race. However, with time, it has been observed that an overemphasis on material interests has created the new uncivilized educated man because material interests and educational interests in such a process of education do not coincide in a meaningful way. Instead, material interests tend to dominate the whole idea of education itself. Given this, I shall be assessing the relevance of non-possessiveness (Aparigraha), which is characterized to be a virtue in Jainism, in education and learning to arrive at a resolution of this problem of the overriding character of material interests to suggest that the purpose of education is to enable a human being to live an informed and enlightened life.
Keywords: education; teaching; learning; value-oriented conduct; education ethics